2015
DOI: 10.2215/cjn.10821014
|View full text |Cite
|
Sign up to set email alerts
|

Focus Group Study of Public Opinion About Paying Living Kidney Donors in Australia

Abstract: Background and objectives The unmet demand for kidney transplantation has generated intense controversy about introducing incentives for living kidney donors to increase donation rates. Such debates may affect public perception and acceptance of living kidney donation. This study aims to describe the range and depth of public opinion on financial reimbursement, compensation, and incentives for living kidney donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 41 publications
0
5
0
1
Order By: Relevance
“…This manner of thematic analysis has similarly been applied in previous focus group studies of patients on renal replacement therapy. [24][25][26][27][28]…”
Section: Discussionmentioning
confidence: 99%
“…This manner of thematic analysis has similarly been applied in previous focus group studies of patients on renal replacement therapy. [24][25][26][27][28]…”
Section: Discussionmentioning
confidence: 99%
“…Public opinion on this matter suggests that aggressively incentivizing donation may not have the effect of dramatically increasing donation rates. In a summary of 12 focus groups conducted in Australia in 2015, Tong et al [34] report that the Australian public generally supported reimbursement for costs Controversies in organ transplantation associated with donation as a way to support living donation. However, this same group found that additional financial incentives in addition to reimbursement of expenses to be 'morally reprehensible.'…”
Section: The Merits and Failings Of Financial Compensation For Living...mentioning
confidence: 99%
“…For some cultural groups, this finding would be ethically challenging and contrary to the perspective of studies suggesting that attaching monetary value to human gametes is deemed disrespectful of ancestral genetic gifts and/or culturally viewed as taboo ( Glover, 2008 ). Moreover, they reflect aspects of the ongoing ethical impasse about the commodification of human life in the context of a burgeoning health industry ( Klitzman and Sauer, 2015a , Klitzman and Sauer, 2015b , Tong et al, 2015 , Gillespie, 2019 ). Alternatively, given the ethically sensitive nature of these items, the finding may simply be a reflection of response bias as the majority of participants were either working in the field or had lived experience of fertility treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to note that responses about concerns may, to some degree, have been shaped by culturally determined ethical attitudes (i.e. both New Zealand and Australia are societies shaped by public perceptions of organ and tissue altruistic donation and civic generosity, where financial inducements may be construed as morally reprehensible and commercially exploitative) ( Hammarberg et al, 2011 , Shaw, 2010 , Tong et al, 2015 ). This may be of particular relevance in New Zealand, where indigenous Māori views of gametes as sacred, the embodiment of genetic lineage and worthy of protection ( Glover, 2008 ) may have shaped community perceptions; indeed, the study results may have been influenced by the increased representation of New Zealand over Australian research participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation